2022
DOI: 10.1101/2022.08.07.503074
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optogenetic activation of dorsal raphe serotonin neurons induces brain-wide activation

Abstract: Serotonin is a neuromodulator that affects multiple behavioral and cognitive functions. Nonetheless, how serotonin causes such a variety of effects through its brain-wide projections and variety of receptors remains unclear. Here we measured the brain-wide response to optogenetic stimulation of serotonin neurons in the dorsal raphe nucleus (DRN) by functional MRI using an 11.7T scanner with a cryoprobe. Transient activation of DRN serotonin neurons caused wide-spread activation of reward-related brain areas. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Another option would be to utilise manipulations of molecular systems within animal models, as recently done by Salvan and colleagues ( Salvan et al, 2022 ) to show that pharmacological and optogenetic manipulation of the serotonergic system modulates the SRNs in a receptor sub-system-specific manner. A similar study has also recently shown that the serotonin receptor gene expression patterns explain a large proportion of the variance in the BOLD signal following optogenetic stimulation of the dorsal raphe ( Hamada et al, 2022 ). Future methodological work expanding the scope of this approach beyond serotonin will be an important step forward to inspect construct validity across neurotransmitter systems.…”
Section: Molecular-enriched Network Analysesmentioning
confidence: 70%
“…Another option would be to utilise manipulations of molecular systems within animal models, as recently done by Salvan and colleagues ( Salvan et al, 2022 ) to show that pharmacological and optogenetic manipulation of the serotonergic system modulates the SRNs in a receptor sub-system-specific manner. A similar study has also recently shown that the serotonin receptor gene expression patterns explain a large proportion of the variance in the BOLD signal following optogenetic stimulation of the dorsal raphe ( Hamada et al, 2022 ). Future methodological work expanding the scope of this approach beyond serotonin will be an important step forward to inspect construct validity across neurotransmitter systems.…”
Section: Molecular-enriched Network Analysesmentioning
confidence: 70%
“…Another option would be to utilise manipulations of molecular systems within animal models, as recently done by Salvan and colleagues (Salvan et al, 2022) to show that pharmacological and optogenetic manipulation of the serotonergic system modulates the SRNs in a receptor sub-system-specific manner. A similar study has also recently shown that the serotonin receptor gene expression patterns explain a large proportion of the variance in the BOLD signal following optogenetic stimulation of the dorsal raphe (Hamada et al, 2022). Future methodological work expanding the scope of this approach beyond serotonin will be an important step forward to inspect construct validity across neurotransmitter systems.…”
Section: Methodical Considerations and Limitationsmentioning
confidence: 84%
“…Since increasing spatiotemporal resolution leads to a reduction in SNR of the images, accessing the highest field MRI available, as well as maximizing the efficiency of the Radio Frequency (RF) transceiver signal is critical. Although cryoprobes have been well implemented to boost SNR, construction limitations of the superconducting environment constrain the usable space and flexibility to accommodate other imaging/recording modalities(13, 6772). Implantable coils have been used in animal imaging for over three decades(12, 7379).…”
Section: Introductionmentioning
confidence: 99%